2015
DOI: 10.1103/physrevb.92.134517
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of superconductivity to structural disorder inSr0.3(NH2)y(NH3)1

Abstract: . (2015) 'Robustness of superconductivity to structural disorder in Sr0.3(NH2)y(NH3)1yFe2Se2.', Physical review B., 92 (13). p. 134517.Further information on publisher's website:http://dx.doi.org/10.1103/PhysRevB. 92.134517 Publisher's copyright statement:Reprinted with permission from the American Physical Society: Physical Review B 92, 134517 c 2015 by the American Physical Society. Readers may view, browse, and/or download material for temporary copying purposes only, provided these uses are for noncomme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Using a similar liquid ammonia route, alkaline earth metals can also be intercalated into FeSe, despite achieving a slightly lower T c than the alkali metals. For Sr and Ba intercalation, the T c is found to be 35 K , and 36 K, respectively. Nonetheless, the compounds are quite remarkable considering that they cannot be prepared by conventional solid-state methods.…”
Section: Intercalation Chemistrymentioning
confidence: 95%
“…Using a similar liquid ammonia route, alkaline earth metals can also be intercalated into FeSe, despite achieving a slightly lower T c than the alkali metals. For Sr and Ba intercalation, the T c is found to be 35 K , and 36 K, respectively. Nonetheless, the compounds are quite remarkable considering that they cannot be prepared by conventional solid-state methods.…”
Section: Intercalation Chemistrymentioning
confidence: 95%
“…[15][16][17][18] Since FeCh tetrahedra could be incorporated in different superconducting materials, it is of interest to study critical currents and vortex pinning mechanism in tetragonal FeS. [19][20][21] Moreover, vortex pinning and dynamics is strongly related to coherence length and superconducting pairing mechanism.…”
Section: 14mentioning
confidence: 99%
“…Several groups soon demonstrated that a host of different electropositive metals besides lithium such as potassium, rare earths, and alkaline earths could be interca- lated into the FeSe sheets through the liquid ammonia method. [128,129,130,131,132] Ying et al found that the amount of K + cations inserted was more important for affecting T c than the amount of ammonia intercalated. [127] In their phase diagram, shown in Figure 12, the superconducting regime does not have a dome-like appearance but rather resembles three flat plateaus.…”
Section: Metal Intercalation With Liquid Ammoniamentioning
confidence: 99%